1990
DOI: 10.1002/j.1460-2075.1990.tb07910.x
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae 3-methyladenine DNA glycosylase has homology to the AlkA glycosylase of E. coli and is induced in response to DNA alkylation damage.

Abstract: We previously cloned a DNA fragment from Saccharomyces cerevisiae that suppressed the alkylation sensitivity of Escherichia coli glycosylase deficient mutants and we showed that it apparently contained a gene for 3‐methyl‐adenine DNA glycosylase (MAG). Here we establish the identity of the MAG gene by sequence analysis and describe its in vivo function and expression in yeast cells. The MAG DNA glycosylase specifically protects yeast cells against the killing effects of alkylating agents. It does not protect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 73 publications
5
96
1
1
Order By: Relevance
“…AlkA is, however, clearly related to the S. cere isiae protein MAG [122][123][124] and to the S. pombe protein Mag1 [125]. In contrast, the single MPG identified in human, rat and murine cells is unrelated to bacterial and yeast glycosylases.…”
Section: Genes For Alkylbase-dna Glycosylasesmentioning
confidence: 85%
See 1 more Smart Citation
“…AlkA is, however, clearly related to the S. cere isiae protein MAG [122][123][124] and to the S. pombe protein Mag1 [125]. In contrast, the single MPG identified in human, rat and murine cells is unrelated to bacterial and yeast glycosylases.…”
Section: Genes For Alkylbase-dna Glycosylasesmentioning
confidence: 85%
“…N-glycosylases that excise alkylated bases have been identified in E. coli (Tag and AlkA), [117][118][119], other bacteria [120,121], Saccharomyces cere isiae (MAG) [122][123][124], Schizosaccharomyces pombe (Mag1) [125], plants [3-meA-DNA glycosylase (MPG)] [126] and mammalian cells (MPG) [127][128][129][130][131][132][133]. These studies have demonstrated that AlkA and yeast glycosylases are related, whereas plant and mammalian alkyl-DNA glycosylases constitute a different family.…”
Section: Dna Glycosylases For Alkylated Basesmentioning
confidence: 99%
“…MMS doses that had no effect on survival of the wild type allowed less than 0.01% survival of 3MeA DNA glycosylase-deficient E. coli (8). Similarly, in S. cerevisiae, doses of MMS that allowed greater than 10% survival in the wild type allowed less than 0.0001% survival in mag1 S. cerevisiae (9). The contribution of 3MeA DNA glycosylase activity to MMS sensitivity of mammalian cells was more modest but nevertheless significant; MMS doses that allowed approximately 10% survival of the wild type caused less than 1% survival of 3MeA DNA glycosylase-deficient Aag Ϫ/Ϫ null cells (12).…”
Section: Discussionmentioning
confidence: 97%
“…The budding yeast Saccharomyces cerevisiae, upon exposure to non-lethal levels of alkylating agents, induces the expression of Mag, the 3MeA DNA glycosylase encoded by the MAG gene [10]. Mag shares significant structural and functional homology with the similarly inducible E. coli 3MeA DNA glycosylase, namely AlkA ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%